Methodological approaches of Spanish professional football academies - Fernández, J.; Borrallo, A.; Vilanova, A.; Balagué, N. (International Journal of Sports Science & Coaching, 2025)
The growing importance of football methodology has led to the creation of specialized departments within professional clubs. Spanish professional football academies, popular around the world, have been pioneers in introducing holistic and complex systems approaches to training methodologies, which initially sparked some controversies and caused epistemological confusion. This study aims to identify the methodological approaches used by Spanish professional football academies, and explore their theoretical and practical coherence. Nine methodology department coordinators, representing a cross-section of the target sample, voluntarily agreed to participate in the study. They responded a semi-structured interview covering: (a) the theoretical foundations of their training methodologies, (b) the consistency between the theoretical principles and the practical applications, and (c) the interactions among specialists from different club sections and the alignment between the methodologies applied in the academy and the first team. The interviews were analyzed using reflexive thematic analysis (RTA). A qualitative content analysis revealed a dominant lack of epistemological coherence both among and within participants, a disconnect between their theoretical frameworks and practical applications, and an inexistent or insufficient dialogue among experts and sections within the same club, along with a lack of alignment between the methodologies applied in the academy and the first team. These inconsistencies and lack of coordination may hinder both players performance and health. In conclusion, coaches` education in complex systems science is proposed to clarify epistemological inconsistencies, empower them to create and contextualize training methodologies, bridge the gap between theory and practice, and enhance collaboration with other professionals.